Supporting teacher learning during the professional development experience: The case of national board certification - Laura Handler; Teresa Petty; Amy Good (Arizona State University, 2021)
Amidst increasing globalized pressures to raise student achievement, nations are heavily investing in various forms of teacher professional development. In the United States, teachers are increasingly electing to pursue National Board Certification, yet few studies have analyzed the experience within the greater complex system of teaching and learning. Viewed from this approach, findings from this study suggest that numerous dynamic forces-relationships, partnerships, structures, and policies-interact in various patterns that can potentially support effective teacher professional development. Implications suggest a need for broader conceptualization, greater cohesion, and more strategic integration of teacher learning in education policy.